Aktivitas Marketing Public Relations @Mahijaproject di Instagram - Nanda Nabila Zavirah; Ani Yuningsih (UNISBA Press, 2024)
Abstract. Seeing the competitive conditions in the creative field which are becoming increasingly difficult day by day, the Mahija Project needs a way to create Marketing Public Relations on Instagram to optimize its role and function in attracting consumer interest. To achieve this goal, Mahija Project describes the positioning of Mahija Project's digital content on Instagram by including the unique products and services offered by @mahijaproject. Apart from that, Mahija Project is taking steps to build a good brand reputation. This research uses a qualitative case study research method and uses the Konstruktiivism paradigm. The purpose of this research is to find out how Public Relations @mahijaproject works to create Marketing Public Relations, especially through social media, social media and Instagram, and to find out how Public Relations @mahijaproject manages brand reputation through the products and services offered by @mahijaproject. Abstrak. Melihat kondisi yang kompetitif di bidang kreatif yang semakin hari semakin sulit ini, Mahija Project membutuhkan cara untuk membuat Marketing Public Relations di Instagram untuk mengoptimalkan peran dan fungsinya dalam menarik minat konsumen. Untuk mencapai tujuan ini Mahija Project menjabarkan positioning konten digital Mahija Project di Instagram dengan memuat keunikan produk dan jasa yang ditawarkan @mahijaproject. Selain itu, Mahija Project membuat langkah-langkah membangun brand reputation yang baik. Penelitian ini menggunakan metode penelitian kualitatif studi kasus dan meinggunakan paradiigma Konstruktiiviismei. Tujuan penelitian ini adalah untuk meingeitahuii bagaiimana cara Public Relations @mahijaproject beikeirja untuk meimbuat Marketing Public Relations khususnya meilaluii meidiia sociial Iinstagram meireika dan untuk meingeitahuii bagaiimana Public Relations @mahijaproject meingeilola brand reiputatiion meilaluii produk dan jasa yang diitawarkan @mahijaproject.